Plant Immune Memory in Systemic Tissue Does Not Involve Changes in Rapid Calcium Signaling - Eichstädt, Bernadette; Lederer, Sarah; Trempel, Fabian; Jiang, Xiyuan; Guerra, Tiziana; Waadt, Rainer; Lee, Justin; Liese, Anja; Romeis, Tina (Frontiers in Plant Science, 2021)
Upon pathogen recognition, a transient rise in cytoplasmic calcium levels is one of the earliest events in plants and a prerequisite for defence initiation and signal propagation from a local site to systemic plant tissues. However, it is unclear if calcium signalling differs in the context of priming: Do plants exposed to a first pathogen stimulus and have consequently established systemic acquired resistance (SAR) display altered calcium responses to a second pathogen stimulus? Several calcium indicator systems including aequorin, YC3.6 or R-GECO1 have been used to document local calcium responses to the bacterial flg22 peptide but systemic calcium imaging within a single plant remains a technical challenge. Here, we report on an experimental approach to monitor flg22-induced calcium responses in systemic leaves of primed plants. The calcium-dependent protein kinase CPK5 is a key calcium sensor and regulator of the NADPH oxidase RBOHD and plays a role in the systemic calcium-ROS signal propagation. We therefore compared flg22-induced cytoplasmic calcium changes in Arabidopsis wild-type, cpk5 mutant and CPK5-overexpressing plants (exhibiting constitutive priming) by introgressing the calcium indicator R-GECO1-mTurquoise that allows internal normalization through mTurquoise fluorescence. Aequorin-based analyses were included for comparison. Based on the R-GECO1-mTurquoise data, CPK5-OE appears to reinforce an “oscillatory-like” Ca2+ signature in flg22-treated local tissues. However, no change was observed in the flg22-induced calcium response in the systemic tissues of plants that had been pre-challenged by a priming stimulus - neither in wild-type nor in cpk5 or CPK5-OE-lines. These data indicate that the mechanistic manifestation of a plant immune memory in distal plant parts required for enhanced pathogen resistance does not include changes in rapid calcium signalling upstream of CPK5 but rather relies on downstream defence responses.